Mastering primary English - Jolliffe, Wendy; Waugh, David (David G.) (London Bloomsbury Academic, 2018)
"Mastering Primary English introduces the primary English curriculum and helps trainees and teachers learn how to plan and teach inspiring lessons that make English learning irresistible. Topics covered include: ¨ Current developments in English ¨ English as an irresistible activity ¨ English as a practical activity ¨ Skills to develop in English ¨ Promoting curiosity ¨ Assessing children in English ¨ Practical issues This guide includes examples of children's work, case studies, readings to reflect upon and reflective questions that all help to exemplify what is considered to be best and most innovative practice. The book draws on the experience of two leading professionals in primary English, Wendy Jolliffe and David Waugh, to provide the essential guide to teaching English for all trainee and qualified primary teachers"--Provided by publisher.
An introduction to primary English -- Current developments in the teaching of Primary English -- English as an irresistible activity: promoting creativity in English -- English as a practical activity: being a reader -- Skills to develop in English: developing the four modes of language -- Children's ideas: engaging children with writing -- Assessing children in English -- Practical issues: challenges for trainee and beginner teachers.
Includes bibliographical references and index.
Keywords: English language -- Study and teaching (Primary); English literature -- Study and teaching (Primary); Language arts (Primary)